Mechanically Robust Nanofibrous Xerogel Membrane for One‐Pass Removal of Trace Water in Oil. Issue 10 (3rd July 2019) - Yang, Xue; Wang, Na; He, Hongwei; Chen, Fuxing; Yang, Yuyan; Ning, Xin
Abstract: Removal of trace water from oil is essential for a high‐performance fuel supply system. Trace water in fuel is a crucial contributor to frequent system maintenance and failure. In this work, an electrospun polyacrylic acid/polyvinyl alcohol (PAA/PVA) nanofibrous xerogel membrane (NFM) is prepared to remove trace water in oil. Based on the optimization of the weight ratio and the crosslinking conditions of PAA/PVA, the resultant NFM shows remarkable water‐retaining capacity (swelling ratio of 124.8 g/g) and rapid absorption property. The optimal membrane displays a small average pore size of 523.2 nm, high porosity of 79.6% as well as robust tensile strength of 8.1 MPa. Additionally, after just one pass through a single layer membrane (thickness of 35 ± 3 µm and areal density of 3.5 ± 0.5 g m −2 ), the milky oil containing 1 wt% water is clarified and the water content reduced to 130 ppm. With extensive water being absorbed into the 3D network (different with the conventional separation mechanism) as well as good compatibility with oil, a multilayer pleated scheme may provide a practical methodology for enhancing fuel oil properties and performances. Abstract : A nanofibrous xerogel membrane is fabricated by electrospinning and thermal induced crosslinking. Based on the construction of the porous structure and attraction of hydrogen bonding among the polymer macromolecule and water, extensive water is maintained in the crosslinked 3D network. This work may provide a facile and promising methodology for one‐step removal of trace water in oil and analytical reagents.